2013
DOI: 10.1002/mnfr.201300146
|View full text |Cite
|
Sign up to set email alerts
|

Dietary grape seed extract ameliorates symptoms of inflammatory bowel disease in IL10‐deficient mice

Abstract: Grape seed extract (GSE) is a by-product of the wine industry, with abundant polyphenolic compounds known for their anti-inflammatory and anti-oxidative effects. Using IL10-deficient mice (IL10KO), here we showed that GSE (1% of dry feed weight) ameliorated inflammatory bowel disease (IBD) indices, increased colonic goblet cell numbers and decreased myeloperoxidase levels in the large intestine. Concomitantly, GSE supplementation attenuated inflammation, decreased the expression of pore forming tight junction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 30 publications
8
61
0
Order By: Relevance
“…Consistently, the present study showed that MO enhanced inflammatory responses in the ileum of NOD female offspring mice. MO impaired intestinal barrier function in offspring, which is associated with decreased goblet cells, increased claudin 2 content and increased phosphorylation of MLC2, all of which are commonly associated with impaired barrier function [27, 33, 34]. The gut system is the first line of defence to oral antigens by either launching immune response or developing tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the present study showed that MO enhanced inflammatory responses in the ileum of NOD female offspring mice. MO impaired intestinal barrier function in offspring, which is associated with decreased goblet cells, increased claudin 2 content and increased phosphorylation of MLC2, all of which are commonly associated with impaired barrier function [27, 33, 34]. The gut system is the first line of defence to oral antigens by either launching immune response or developing tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, GP polyphenolics quenched ROS production in Caco-2 cells bringing it lower than the control with no detrimental effect of extrusion cooking. GP polyphenolics possess antioxidant as well as anti-infla mmatory effects with a well-established health beneficial effect on intestine [9,12,45,46]. These finding suggest that GP can be used as adjunctive ingredient in the production of healthy extrusion based cornstarch expended products.…”
Section: Effect Of Gp Extrudates Extracts On Intracellular Ros Producmentioning
confidence: 92%
“…GP also contains substantial amount of non-digestible fiber (60%-70%), essential fatty acids (13%-19%), proteins (11%), as well as non-phenolic tocopherols, betacarotene, and minerals [6,7]. The polyphenolics from GP are known for their antioxidant and anti-inflammatory effects [8,9], which demonstrate preventive effects on cancer [10], cardiovascular diseases [11], and inflammatory bowel disease [12]. The GP polyphenolics have been used in food technology as antioxidants to inhibit the oxidation of fish lipids, frozen fish muscle, and fish oil [13].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of specific intestinal bacterial groups was measured by qPCR. Genus- or species-specific 16S rRNA gene primers were used as described previously [13]. Primer sequences are listed in the Additional file 1: Table S2.…”
Section: Methodsmentioning
confidence: 99%